Japanese Polytechnic Diplomacy in Indonesia: Establishing Electrical Engineering Polytechnic Institute of Surabaya (EEPIS) as Japan’s Higher Vocational Ambassador to Developing Countries through Triangular Development Cooperation - Siti Rokhmawati Susanto (Jurnal Hubungan Internasional, 2021)
This paper aims to examine implications of Japan’s ‘polytechnic diplomacy’approach as its international development strategy towards Indonesia. Utilizingconcepts and framework related to international development assistance,triangular development cooperation (TDC), and public diplomacy, this paperargues that development fund disbursement affects interactions among actors,not only in bilateral context but also multilaterally. Mainly, on how this activitytransform an aid recipient into a potential partner for the donor’s futureinternational development programs. It is occurred due to the facilitation ofdonor’s triangular development cooperation (TDC). The aid recipient’s successstory thus prompted the donor to perceive them as its development ambassador.the pattern continues as the donor attempts to disseminate the formula to otherdeveloping countries. The Electrical Engineering Polytechnic of Surabaya(EEPIS) exemplifies the case on how a specific foreign aid approach raises globalmultiplier effects to both aid provider and recipient.